The Scarcity in Islamic Perspective : an Analysis of Cooking Oil Scarcity in Indonesia - Putra, Adiyes; Nurnasrina, Nurnasrina (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2023)
Abstract The study is look at the views of Islamic economists on scarcity and compares them with western economists, then provides conclusions on scarcity, especially the scarcity of cooking oil in Indonesia from the perspective of Islamic macroeconomics. Research methods are classified as qualitative methods based on the source of the problem from observations, and finding solutions based on the results of processed data from readings and the views of economists, both those found from research results published in journals or books related to scarcity and Islamic macroeconomics. Research result; The scientific background between Muslim scholars and western scholars causes different views between them. In the view of Islam, Allah SWT has created the universe as a complete resource to support human life, so there is no scarcity according to Islam, which exists only as a test and human greed. In the case of the scarcity of cooking oil based on the findings, the scarcity is caused by deviant behaviour by entrepreneurs, distributors, and the government. Taking into account the results of the analysis, it is hoped that stakeholders, especially the government, will take firm action and routine supervision of economic actors with regulations from producers, distributors, and regulators themselves. This is an effort to ensure that the distribution system, especially the distribution of cooking oil from upstream to downstream, runs normally, without any behaviour that can harm the general public. Discussions related to scarcity have been widely discussed by researchers, but related to the emergence of cooking oil scarcity in Indonesia as the world's largest palm oil-producing country is an irony. To the best of the researcher's knowledge, this is the first study on the scarcity of cooking oil from an Islamic macroeconomic perspective. Keywords: Scarcity, Islamic economics, Islamic Macroeconomics, Deviant Behavior Paper Type; Conceptual paper Abstrak Kajian dalam penelitian ini melihat kelangkaan menurut pandangan para ekonom Islam dan membandingkannya dengan pandangan ekonom barat, kemudian memberikan kesimpulan mengenai kelangkaan khususnya kelangkaan minyak goreng di Indonesia dari perspektif makroekonomi Islam. Metode penelitian tergolong metode kualitatif berdasarkan sumber permasalahan dari observasi, dan pencarian solusi berdasarkan hasil olah data dari bacaan dan pandangan para ekonom, baik yang ditemukan dari hasil penelitian yang dimuat dalam jurnal atau buku yang berkaitan dengan kelangkaan. Hasil penelitian; Latar belakang keilmuan antara cendekiawan muslim dan cendekiawan barat menimbulkan perbedaan pandangan di antara mereka. Dalam pandangan Islam, Allah SWT telah menciptakan alam semesta sebagai sumber daya yang lengkap untuk menunjang kehidupan manusia, sehingga tidak ada kelangkaan menurut Islam, yang ada hanya sebagai ujian dan keserakahan manusia. Dalam kasus kelangkaan minyak goreng berdasarkan temuan, kelangkaan tersebut disebabkan oleh perilaku menyimpang yang dilakukan oleh pengusaha, distributor, dan pemerintah. Dengan memperhatikan hasil analisis tersebut, diharapkan para pemangku kepentingan khususnya pemerintah dapat mengambil tindakan tegas dan melakukan pengawasan rutin terhadap para pelaku ekonomi dengan adanya regulasi dari produsen, distributor, dan regulator itu sendiri. Hal ini sebagai upaya untuk memastikan sistem distribusi, khususnya distribusi minyak goreng dari hulu hingga hilir, berjalan normal, tanpa adanya perilaku yang dapat merugikan masyarakat luas. Pembahasan terkait kelangkaan telah banyak dibicarakan oleh para peneliti, Namun terkait munculnya kelangkaan minyak goreng di Indonesia sebagai negara penghasil minyak sawit terbesar di dunia adalah sebuah ironi. Sejauh pengetahuan peneliti, ini adalah studi pertama tentang kelangkaan minyak goreng dari perspektif makroekonomi Islam. Kata kunci: Kelangkaan, Ekonomi Islam, Makroekonomi Islam, Perilaku Menyimpang Jenis Kertas; Makalah konseptual